Research on Industrial Product Design Integrating Consumer Psychological Analysis - Xiong, Hao; Ran, Bei (Transactions on Social Science, Education and Humanities Research, 2023)
Industrial product design should meet the aesthetic requirements of consumers, and as a designer, attention should be paid to the area where the product is located. How to better attract consumers and stimulate their purchasing desire fundamentally depends on the design of industrial products. This article provides a thorough and detailed understanding of consumers’ living habits, psychology, aesthetic habits, etc., in order to make their works accepted by consumers and maintain a stronger vitality. Design psychology is a branch of psychology, and the industrial production process of products cannot be separated from the packaging process. Packaging design is a crucial aspect and an important factor in attracting consumers. Consumers with a positive attitude towards product requirements determine the unique form of design expression. The techniques used in design can be exaggerated, mischievous, playful, bizarre, etc. All words that can be used to describe people’s inner thoughts are transformed into design styles here. Therefore, the design of a product must have novelty and attractiveness in order to give consumers the desire to further understand the product and stimulate their purchasing psychology.